Analyzing public opinion toward the 2019 North Korea–United States summit through mining twitter. Issue 1 (18th October 2019) - Kim, Jaewon; Kim, Ji‐young; Zhu, Yongjun
ABSTRACT: The study aims to understand public opinion toward the 2019 North Korea–United States summit. Specifically, we investigate the changes in public opinion before and after the summit through comparing and analyzing networks of major keywords extracted from Twitter. We found a clear difference between public opinion before and after the summit. For example, we could see that the differences in public perception of End of war, peace, and freedom changed. The clear difference between Chinese and South Korean representatives can be interpreted as to how international relations and domestic situation lead to public opinion. This study shows that network analysis can be useful for quantitative public opinion analysis.